The Impact of Delay: Evidence from Formal Out-of-Court Restructuring - Stjepan Srhoj; Dejan Kovač; Jacob N. Shapiro; Randall Filer (Center for Economic Studies and ifo Institute (CESifo), 2021)
Bankruptcy restructuring procedures are used in most legal systems to decide the fate of businesses facing financial hardship. We study how bargaining failures in such procedures impact the economic performance of participating firms in the context of Croatia, which introduced a "pre-bankruptcy settlement" (PBS) process in the wake of the Great Recession of 2007 - 2009. Local institutions left over from the communist era provide annual financial statements for both sides of more than 180,000 debtor-creditor pairs, enabling us to address selection into failed negotiations by matching a rich set of creditor and debtor characteristics. Failures to settle at the PBS stage due to idiosyncratic bargaining problems, which effectively delays entry into the standard bankruptcy procedure, leads to a lower rate of survival among debtors as well as re-duced employment, revenue, and profits. We also track how bargaining failures diffuse through the network of creditors, finding a significant negative effect on small creditors, but not others. Our results highlight the impact of delay and the importance of structuring bankruptcy procedures to rapidly resolve uncertainty about firms' future prospects.
Keywords: G33; G34; D02; L38; P37; 330; bankruptcy; insolvency; liquidation; restructuring